Shakespeare's secret - Broach, Elise (New York : Square Fish, 2005)
Named after a character in a Shakespeare play, misfit sixth-grader Hero becomes interested in exploring this unusual connection because of a valuable diamond supposedly hidden in her new house, an intriguing neighbor, and the unexpected attention of the most popular boy in school.
Notable/Best Books (A.L.A.).
Wilson's Children.
Wilson's Junior High School.
6.1
5-8
Keywords: Shakespeare, William, -- 1564-1616 -- Authorship -- Juvenile fiction; Shakespeare, William, -- 1564-1616 -- Authorship -- Fiction; Shakespeare, William, -- 1564-1616 -- Authorship -- Fiction; Mystery and detective stories; Neighbors -- Juvenile fiction; Mystery and detective stories; Neighbors -- Fiction; Mystery fiction; Neighbors -- Fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Juvenile fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Juvenile fiction; Maryland -- Juvenile fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction; Maryland -- Fiction; Great Britain -- History -- 1485-1603, Tudors -- Fiction; Maryland -- Fiction